PENGARUH PEMBELAJARAN KOOPERATIF TIPE STUDENT FACILITATOR AND EXPLAINING TERHADAP HASIL BELAJAR SISWA PADA MATERI STATISTIKA - Domu, Ichdar; Monoarfa, Jorry; Mangimpis, Enad (Universitas Negeri Manado, 2020)
The porpuse of this research was to determiner whether the average of the students learning outcomes on the statistic lesson whom used the student facilitator dan explaining learning model were higher than the the problem based learning model. This research was conducted at SMP Negeri 2 Tondano during the even semester of the 2018/2019 academic year. This research categorized as quasi-experimental. The subject in this reseach were students class VII E and students class VIII F. The analysis data, conducted the average of the students learning outcomes whom used the cooperative type the students facilitator model and explaining model was 81,875, while the average of the students learning outcomes used the problem based learning model was 65.625. So can be concluded, that the average of the students learning outcomes those used the cooperative learning type the students facilitator and explaining model were higher than whom used the problem based learning.Â Key Words: Learning Outcomes, Statistic, Student Facilitator dan Explaining